A commentary on the whole Bible ; v. 2 - Poole, Matthew, 1624-1679 (London, UK Banner of Truth, 1962)
Contents : v. 2 : Psalms - Malachi
"This work was originally published under the title " Annotations on the Holy Bible" in two volumes - Vol. 1 (Genesis to Isaiah), in 1683 and Vol. 2 (Jeremiah to Revelation) in 1685." Completed posthumously (from Isaiah 58 onwards) by various colleagues drawing largely from Pooles own " Synopsis Critorum"...
Keywords: Bible -- commentaries